2016
DOI: 10.19080/artoaj.2016.02.555587
|View full text |Cite
|
Sign up to set email alerts
|

Oron Nutrition of Crops in Relation to Yield and Quality- A Review

Abstract: Boron nutrition of soil and crops has assumed greater importance with the introduction of high yielding crop varieties under intensive cultivation with high use of chemical fertilizers. The availability and transformation of boron in soil, yield and quality of crops have a significant bearing in relation to boron and sulphur nutrition. Use of optimum combination of organic, inorganic and biological nutrient sources in a specific crop, cropping system and climatic situation so as to achieve and to sustain the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Boric acid is a chemical compound that occurs naturally and is composed of hydrogen, oxygen, and boron. It can be found naturally in almost all fruits and vegetables, as well as in some nuts and grains, and can also be mined from the ground [ 172 , 173 ]. Generally, boric acid is a nonhazardous substitute for chemical flame retardants that has been extensively studied and consistently deemed to have low toxicity for both animals and humans, and is listed as a noncarcinogen by the US EPA [ 174 ].…”
Section: Flame Retardant Coating Formulations and Designs: The Implem...mentioning
confidence: 99%
“…Boric acid is a chemical compound that occurs naturally and is composed of hydrogen, oxygen, and boron. It can be found naturally in almost all fruits and vegetables, as well as in some nuts and grains, and can also be mined from the ground [ 172 , 173 ]. Generally, boric acid is a nonhazardous substitute for chemical flame retardants that has been extensively studied and consistently deemed to have low toxicity for both animals and humans, and is listed as a noncarcinogen by the US EPA [ 174 ].…”
Section: Flame Retardant Coating Formulations and Designs: The Implem...mentioning
confidence: 99%
“…Sulphur and boron play important roles in improving the production phenology of mustard (number of siliqua/plant and test weight of seeds) and the crop also responded well to application of 20 kg S ha −1 and 1 kg B ha −1 [3]. Boron also plays a vital role in cell wall synthesis, root elongation, glucose metabolism, nucleic acid synthesis, lignification and tissue differentiation [4]. Arvind et al [5] also reported that soil application of @ 50 kg S and 2 kg B ha −1 along with recommended dose of NPK fertilizers produced higher yield of sesame grown in an upland red soil of Vindhyan zone of eastern part of Uttar Pradesh which was highly deficient in S and B. Kalaiyarasan et al [6] also noted that application of 60 kg S + 1 kg B ha −1 resulted the highest growth, yield attributes and yield, quality and nutrient uptake of hybrid sunflower (cv.…”
Section: Introductionmentioning
confidence: 99%